2019
DOI: 10.1186/s13104-019-4768-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum 25-hydroxyvitamin D3 concentration is associated with higher pain and disability in subjects with low back pain: a case–control study

Abstract: ObjectivesLow back pain (LBP) is a common medical problem worldwide. The aim of this study is to evaluate the association between serum concentration of 25-hydroxivitamin D3 and functional disability in patients suffering from LBP in a sample of Azeri middle-aged subjects, North West of Iran.ResultsIn this case–control study, 63 eligible patients with LBP and 55 healthy subjects enrolled in the study. Peripheral venous blood was taken for evaluating the serum concentration of 25-hydroxivitamin D3. We recognize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Age-dependent IDD, often associated with osteoporosis-whose treatment aimed at increasing the bone mineral density includes vitamin D supplementation-have been suggested as being responsible of endplate calcification by blocking nutrient and oxygen supply in the disc [15]. Nevertheless, it was observed that subjects with deficiency or insufficiency of vitamin D were more likely to exhibit low back pain than subjects with a normal serum concentration [16][17][18], even if also in this case conflicting evidence is reported [19]. Therefore, the increasingly recognized immunomodulatory role of vitamin D [20,21] could be exploited to target the inflammatory and catabolic process in the IDD [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Age-dependent IDD, often associated with osteoporosis-whose treatment aimed at increasing the bone mineral density includes vitamin D supplementation-have been suggested as being responsible of endplate calcification by blocking nutrient and oxygen supply in the disc [15]. Nevertheless, it was observed that subjects with deficiency or insufficiency of vitamin D were more likely to exhibit low back pain than subjects with a normal serum concentration [16][17][18], even if also in this case conflicting evidence is reported [19]. Therefore, the increasingly recognized immunomodulatory role of vitamin D [20,21] could be exploited to target the inflammatory and catabolic process in the IDD [22,23].…”
Section: Introductionmentioning
confidence: 99%